Development, Optimization, and Evaluation of New Herbal Antipsoriatic Emulgel - Azza Dawoud H Dawoud; Sali Dawoud Hussien; Mohammed Abdalbagi; Mohamed El Hassan Shayoub (Journal of Pharmaceutical Research)
Psoriasis is recognized as the most common autoimmune disease caused by the inappropriate activation of the cellular immune system, characterized, by severe skin inflammation, epidermal hyperproliferation, the lack of possible cure and associated severe side effects in allopathic medicines has led to extensive research in natural products with antipsoriatic activity. Aloe sinkatana plant is a very potent antipsoriatic agent and is used traditionally to treat psoriasis. To formulate and evaluate a new emulgel from Aloe sinkatana plant extract used as an anti-psoriatic agent. A 2³ factorial design was selected to formulate Aloe sinkatana Eumlgel. The three factors were: the amount of gelling agent X1, amount of emulsifying agent X2, and amount of liquid paraffin X3, these were selected as independent formulation variables, while the viscosity and spreadability were taken as dependent variables or response variables. The model of the formulation was considered statistically excellent with R² values approaching unity since, the R² values for both the response's viscosity and spreadability were found to be 0.9915, and 0.9761 respectively. The extract of Aloe sinkatana was formulated as an active ingredient in the emulgel dosage form, and formula F3 was selected as an optimal emulgel formula.